The excellent teacher educator professional journey - Hashim, Hashimah; Ismail, Ismi Arif; Abdul Wahat, Nor Wahiza; Idris, Khairuddin (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
This study was conducted to explore professional journey of the excellent teacher educator through their continuous professional education to become expert. Professional expertise development is a long process that often takes many years. Although expertise research is extensive, little attention has been paid to studies that explore how expertise grows over time. This study narrate seven excellent teacher educator professional journey. Data was presented in matric to compare the similarities and differences of their journey to become expert, in order to gain insights on how the experience impacted on the ways in which the excellent teacher educator acclimatized and gradually advanced in proficiency and to understand how the experience changed over time. The study informed that all research participants enter their profession as teachers, became lecturers at teachers training colleges, gradually moving from one to another focus fields before they are recognized for their expertise and practice deliberately on them. This study also informed that expertise of the excellent teacher educators stretched beyond their service in public sectors and after their retirement.